Aspects of Q-ball theory - Lennon, OREV (2021)
Q-balls are an example of non-topological soliton that can appear in the spectrum of scalar field theories. They are semi-classical states that minimise the energy for a given Noether charge. If isolated from other sectors, these spherically symmetric objects are kept absolutely stable by energy and Noether charge conservation. Though the properties of Q-balls cannot be determined analytically in general, progress can be made in two opposite limits: the thin-wall (large charge) limit; and the thick-wall (small charge) limit. Q-balls are both interesting phenomenologically and as formal objects in their own right, as evidenced by the large body of work on this subject.